2017
DOI: 10.2166/ws.2017.134
|View full text |Cite
|
Sign up to set email alerts
|

Experimental assessment of soil effects on the leakage discharge from polyethylene pipes

Abstract: Leaking water from pipes depends on several factors such as pressure, pipe material, types of cracks and holes and also regime of flow through cracks. The effects of these factors on the leakage have been investigated by several researchers. However, few studies have been found considering the effects of soil around the pipes on the leakage discharge. Here, the leakage from polyethylene pipes is simulated in the laboratory, selecting several soils with different specifications. The leak discharge equation is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…The discharge coefficient of the hole is significantly higher than the cracks, while it is higher in free air than in soils. Although [14] investigated the same results for uniform soils, this research confirms their conclusion for non-uniform soils. Figure 6 shows variations in the leakage discharge coefficient in regard to the crack length.…”
Section: The Effect Of Soil Surrounding the Pipe And Crack Length On ...supporting
confidence: 78%
See 2 more Smart Citations
“…The discharge coefficient of the hole is significantly higher than the cracks, while it is higher in free air than in soils. Although [14] investigated the same results for uniform soils, this research confirms their conclusion for non-uniform soils. Figure 6 shows variations in the leakage discharge coefficient in regard to the crack length.…”
Section: The Effect Of Soil Surrounding the Pipe And Crack Length On ...supporting
confidence: 78%
“…Table 2 shows that the value of leakage power for 14, 17 and 20 mm cracks is between 0.86 and 1.91. However, the value of the leakage exponent for the hole used in the present study was observed to be slightly less than 0.5, which may be due to the elasticity of the polyethylene material [14].…”
Section: Leakage Type Equation Surrounding Conditioncontrasting
confidence: 65%
See 1 more Smart Citation
“…P = P atm = 0 (gage). It is true that the leakage flow rate modeled in the absence of soils (outlet to atmospheric pressure), as assumed in our study and in most of the laboratory relations (Equations 1, 2, and 4) used in the computational models, may be higher compared to those of field conditions with the presence of soil (Latifi et al, 2018). Nevertheless, for high soil diffusibility (e.g.…”
Section: Methodsmentioning
confidence: 83%